2007
DOI: 10.1167/iovs.06-0296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TGF-β2, BMP-4, and Gremlin in the Trabecular Meshwork: Implications for Glaucoma

Abstract: These results are consistent with the hypothesis that, in POAG, elevated expression of Gremlin by TM cells inhibits BMP-4 antagonism of TGF-beta2 and leads to increased ECM deposition and elevated IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
203
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 208 publications
(208 citation statements)
references
References 37 publications
5
203
0
Order By: Relevance
“…(Liton et al 2006) The fibronectin change and perhaps other aspects of this study could be related to TGFβ2, BMP-4 and Gremlin studies recently reported. (Wordinger et al 2007) In other studies of glaucomatous outflow tissue, calcification markers relating to matrix Gla protein and BMP-2 action appear to be modified, although mechanisms remain to be established. (Xue et al 2006;Xue et al 2007) Increases in soluble CD44, particularly the phosphorylated form, have also been recently linked to glaucoma, although causal relationships remain to be established.…”
Section: Glaucoma and Ecmmentioning
confidence: 98%
“…(Liton et al 2006) The fibronectin change and perhaps other aspects of this study could be related to TGFβ2, BMP-4 and Gremlin studies recently reported. (Wordinger et al 2007) In other studies of glaucomatous outflow tissue, calcification markers relating to matrix Gla protein and BMP-2 action appear to be modified, although mechanisms remain to be established. (Xue et al 2006;Xue et al 2007) Increases in soluble CD44, particularly the phosphorylated form, have also been recently linked to glaucoma, although causal relationships remain to be established.…”
Section: Glaucoma and Ecmmentioning
confidence: 98%
“…We recently discovered that the biological effects of TGF-β in the TM can be modulated by the bone morphogenic proteins (BMPs) and their antagonist gremlin (46). These findings highlight the intricate interrelationships among signaling pathways, because BMP and Wnt signals can interact to coordinate tissue development.…”
Section: Figurementioning
confidence: 99%
“…The canonical BMP pathway and activin and TGFb pathway antagonize one another in numerous physiological contexts, including in early embryonic development, where SMAD2 antagonizes SMAD1 to establish body patterning (Yamamoto et al, 2009), in angiogenesis, where the balance of SMAD1/5/8 and SMAD2/3 establishes an angiogenic switch between activation and resolution phases (Goumans et al, 2003), in cell fate of type 2 alveolar epithelial cells, where trans-differentiation to a type 1 alveolar program is promoted by SMAD2/3, but restricted by SMAD1/5/8 , during maintenance of epithelial cell polarity, where SMAD1/5/8 restricts the TGFbinduced epithelial-mesenchymal transition (Saitoh et al, 2013), and during regulation of skeletal muscle mass, where SMAD1/5/8 and SMAD2/3 signaling inversely impact on muscle hypertrophy (Sartori et al, 2013;Winbanks et al, 2013). Moreover, imbalances in the ratio of TGFb superfamily cytokines are increasingly associated with human diseases, including pulmonary and kidney fibrosis (Izumi et al, 2006;Nguyen and Goldschmeding, 2008), glaucoma (Wordinger et al, 2007;Zode et al, 2009), asthma (Stumm et al, 2014) and pulmonary arterial hypertension Morrell et al, 2001). However, the mechanisms that allow the BMP pathway and the activin and TGFb pathway to antagonize one another remain unclear.…”
Section: Introductionmentioning
confidence: 99%